Spontaneous heterotopic pregnancy: a rare possibility - Chavan, Komal N.; Mayadeo, Lalita N.; Sontakke, Priya N.; Rathod, Heena V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Heterotopic pregnancy is defined as a condition when intrauterine and extrauterine pregnancy occur simultaneously. It is a life-threatening condition that requires immediate and accurate diagnostics and treatment. We present the case of a 34-year-old multigravida in her 7 weeks of gestation came to emergency ward with complains of pain in abdomen for 3 days. Ultrasonographic examination showed a live intrauterine pregnancy and mild to moderate free fluid in abdomen with moving internal echoes. An emergency exploratory laparotomy done and left sided tubal ectopic removed along with right salpingectomy as patient was willing for family planning. A high index of suspicion is required to diagnose Heterotopic pregnancy as clinical as well as radiological findings may be insufficient for diagnosis.